2013
DOI: 10.15580/gjer.2013.7.051413612
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Literacy and World Knowledge amongst Open Distance Learning Students in Zimbabwe

Abstract: In order to succeed in a globally competitive world, it is imperative to acquire knowledge and an understanding of the places and cultures outside the boarders of one's country. Zimbabwe has one of the highest literacy rates in Sub-Saharan Africa but despite this, large gaps exist in the knowledge about the levels of geographic literacy among Zimbabwean students. A survey, adapted from the National Geographic-Roper Global Geographic Literacy Survey, was administered to 103 students (11%) in the Diploma in Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is feared that the fact that weak geographic literacy in women can affect women's wisdom in making decisions in everyday life. Mhishi et al (2013) revealed that of the 103 Zimbabwean students studied, women's geoliteration was lower than that of men. Some researchers also mention the same thing regarding Some researchers also argue that significant differences are related to sex, with men performing better in terms of geographic information and spatial skills compared to women (Bein, 1990;Cross, 1987;Chiodo, 1993;Eve et al, 1994;Genctürk, 2009;Hardwick et al, 2000;NAEP, 1994;National Geographic Roper Survey, 2002;Roper National Geographic Survey, 2006;Nolan, 2002;Oigara, 2006;Thomas, 2001;Torrens, 2001;Wood et al, 1988;Winship, 2004;Güven, 2021).…”
Section: Factors Affecting the Geographic Literacy Of High School Stu...mentioning
confidence: 99%
See 4 more Smart Citations
“…It is feared that the fact that weak geographic literacy in women can affect women's wisdom in making decisions in everyday life. Mhishi et al (2013) revealed that of the 103 Zimbabwean students studied, women's geoliteration was lower than that of men. Some researchers also mention the same thing regarding Some researchers also argue that significant differences are related to sex, with men performing better in terms of geographic information and spatial skills compared to women (Bein, 1990;Cross, 1987;Chiodo, 1993;Eve et al, 1994;Genctürk, 2009;Hardwick et al, 2000;NAEP, 1994;National Geographic Roper Survey, 2002;Roper National Geographic Survey, 2006;Nolan, 2002;Oigara, 2006;Thomas, 2001;Torrens, 2001;Wood et al, 1988;Winship, 2004;Güven, 2021).…”
Section: Factors Affecting the Geographic Literacy Of High School Stu...mentioning
confidence: 99%
“…The theory of deficiency argues that spatial abilities are related to human physiology and hormonal levels and that differences in physiology and hormones between men and women cause differences in spatial abilities (Kitchin, 1996). Mhishi et al (2013) argue that gender factors influence a person's level of geographic literacy. Some researchers also argue that significant differences are related to sex, with men performing better in terms of geographic information and spatial skills compared to women (Güven, 2021).…”
Section: Gender Factorsmentioning
confidence: 99%
See 3 more Smart Citations